The Mediating Role of Early Maladaptive Schemas in the Relationships of Emotional Maltreatment and Emotional Disorders - Abdolahzadeh Rafi, Mahdi; Adibsereshki, Narges; Hasanzadeh Aval, Maryam (European Journal of Mental Health, 2017)
Although the consequences of emotional maltreatment have not been extensively investigated, experiences of emotional maltreatment or abuse have been associated with powerful and enduring psychological problems. The purpose of this study was to explore the extent to which emotional maltreatment contributed to emotional disorders, and the role of Early Maladaptive Schemas (EMS) in relationships of emotional maltreatment and emotional disorders in pre-adolescents. This study used the correlation-modelling design. A total of 492 junior high students participated in the study. The emotional abuse or maltreatment questionnaire made by NOROUZI (2012), the Achenbach self-report emotional disorders questionnaire preadolescence form (ACHENBACH & RESCORLA 2001), and the Early Maladaptive Schemas questionnaire (RIJKEBOER& DE BOO 2010) were used to measure and analyse emotional maltreatment and EMS in the students. The findings indicated that emotional maltreatment can directly lead to emotional disorders (anxiety, affective disorder) and schemas such as loneliness, submission and vulnerability. Emotional maltreatment was a significant predictor of emotional disorders. Findings of this study can inform parents and those who treat children in negative ways (maltreatment) of their impact on children’s emotions and of the negative outcomes.